Transcriptome analysis reveals a de novo DNA element that may interact with chromatin-associated proteins in Plasmodium berghei during erythrocytic development - Adaobi Okafor; Yagoub Adam; Benedikt Brors; Ezekiel Adebiyi (Scientific Reports)
Abstract The life cycle of Plasmodium parasites involves intricate, multistage processes that are tightly regulated by stage-specific transcription factors. These factors bind to regulatory regions within gene promoters, enabling the precise expression of genes required for each developmental stage. Despite the importance of these transcriptional mechanisms, our understanding remains limited, particularly in the rodent model organism P. berghei. To address this, we conducted a genome-wide analysis of RNA-Seq data from different developmental stages of P. berghei by initially integrating data from human malaria parasites P. falciparum and P. vivax. We identified unique transcriptional signatures across Plasmodium species. Our analysis of P. berghei revealed stage-specific gene sets clustered by expression profiles and predicted regulatory motifs involved in their control. We interpreted these motifs using known binding sites for eukaryotic transcription factors including ApiAP2 proteins. Additionally, we expanded the annotation of the AGGTAA motif which resembles a de novo motif linked to erythrocytic development in P. falciparum, and identified its potential interacting proteins including members of the PfMORC and GCN5 complexes. This study enhances our understanding of gene regulation in P. berghei and provides new insights into the transcriptional dynamics underlying Plasmodium development.